Crucial roles of circulating tumor cells in the metastatic cascade and tumor immune escape: biology and clinical translation - Klaus Pantel; Catherine Alix-Panabières (Journal for ImmunoTherapy of Cancer, 2022)
Cancer-related deaths are mainly caused by metastatic spread of tumor cells from the primary lesion to distant sites via the blood circulation. Understanding the mechanisms of blood-borne tumor cell dissemination by the detection and molecular characterization of circulating tumor cells (CTCs) in the blood of patients with cancer has opened a new avenue in cancer research. Recent technical advances have enabled a comprehensive analysis of the CTCs at the genome, transcriptome and protein level as well as first functional studies using patient-derived CTC cell lines. In this review, we describe and discuss how research on CTCs has yielded important insights into the biology of cancer metastasis and the response of patients with cancer to therapies directed against metastatic cells. Future investigations will show whether CTCs leaving their primary site are more vulnerable to attacks by immune effector cells and whether cancer cell dissemination might be the ‘Achilles heel’ of metastatic progression. Here, we focus on the lessons learned from CTC research on the biology of cancer metastasis in patients with particular emphasis on the interactions of CTCs with the immune system. Moreover, we describe and discuss briefly the potential and challenges for implementing CTCs into clinical decision-making including detection of minimal residual disease, monitoring efficacies of systemic therapies and identification of therapeutic targets and resistance mechanisms.